The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/0100-67622016000100005
|View full text |Cite
|
Sign up to set email alerts
|

GAS EXCHANGE IN YOUNG PLANTS OF Tabebuia aurea(Bignoniaceae Juss.) SUBJECTED TO FLOODING STRESS1

Abstract: -The Paratudo (Tabebuia aurea) is a species occurring in the Pantanal of Miranda, Mato Grosso do Sul, Brazil, an area characterized by seasonal flooding. To evaluate the tolerance of this plant to flooding, plants aged four months were grown in flooded soil and in non-flooded soil (control group). Stomatal conductance, transpiration and CO 2 assimilation were measured during the stress (48 days) and recovery (11 days) period, totalling 59 days. The values of stomatal conductance of the control group and stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition, changes in the photosynthetic apparatus and protection mechanisms associated with the activity of antioxidant enzymes also stand out [6] [7] [8] [9].…”
mentioning
confidence: 99%
“…In addition, changes in the photosynthetic apparatus and protection mechanisms associated with the activity of antioxidant enzymes also stand out [6] [7] [8] [9].…”
mentioning
confidence: 99%
“…Under these conditions, plant needs more energy for surviving the flood waters, resulting in a decrease of biosynthesis of secondary metabolites (Irfan et al 2010;Ferner et al 2012). This idea is supported by a recent study, where it was observed that plants of T. aurea subjected to flooding conditions reduce their physiological activities (Oliveira and Gualtieri 2016).…”
Section: Discussionmentioning
confidence: 57%
“…For example, stomatal closure is a commonly reported early response to soil flooding (Pezeshki 2001, Herrera et al 2008). This stomatal closure decreases CO 2 diffusion into the leaf (Farquhar and Sharkey 1982), leading to a decline in photosynthesis (Lavinsky et al 2007, Mielke and Schaffer 2011, Pimentel et al 2014, Oliveira and Gualtieri 2016, a decrease in photosynthate production, followed by a decline in biomass accumulation (Sena Gomes and Kozlowski 1980, Mielke et al 2003, Mielke and Schaffer 2010, Branco et al 2017.…”
Section: Discussionmentioning
confidence: 99%